Effect of cervical cerclage on rate of cervical shortening. (2nd December 2015) - Drassinower, D.; Vink, J.; Pessel, C.; Vani, K.; Brubaker, S. G.; Zork, N.; Ananth, C. V.
ABSTRACT: Objective: Although cerclage has been shown to reduce the risk of recurrent preterm birth in a high‐risk patient population, the mechanism by which this occurs is not well understood. Our objective was to evaluate whether cerclage affects the rate of cervical shortening taking into account exposure to 17‐hydroxyprogesterone and vaginal progesterone. Methods: This was a retrospective cohort study of women who had serial cervical length measurements due to a history of spontaneous preterm delivery. Demographic data, obstetric history, progesterone administration, delivery information and serial cervical length measurements were collected. The rate of cervical shortening was compared in women with and without cerclage. Subgroup analyses were performed to compare rates of cervical shortening by indication for cerclage (history indicated vs ultrasound indicated) and outcome in the current pregnancy (cerclage vs no cerclage among those who delivered preterm). Results: A total of 414 women were included of whom 32.4% ( n  = 134) had a cerclage. There was no difference in the rate of cervical shortening between the cerclage (0.8 mm/week) and no‐cerclage (1.0 mm/week, P  = 0.43) groups. The rates of cervical shortening among history‐indicated and ultrasound‐indicated cerclage groups were similar (0.9 vs  1.3 mm/week, respectively, P  = 0.2). Among patients with a preterm delivery in the index pregnancy, the rates of cervical shortening among those with (1.31 mm/week) and without (1.28 mm/week, P  = 0.78) cerclage were also similar. Conclusion: Cervical shortening among women with cerclage occurs at a similar rate to that among women without a cerclage, regardless of indication for cerclage or pregnancy outcome. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.